Respuesta :

the first one y = 2/3

Answer:

x = 3

y = -2

z = -1.

Step-by-step explanation:

2x -y +z = 7

2x + 4y - 2z = 0

x-y + 3z = 2

Subtracting the second equation from the first:

-5y + 3z = 7  ------------(A)

Multiply the third equation by -2 and adding this to the second equation:

6y -8z = -4 ..................(B)

Multiply A by 8 and B by 3, we get

-40y + 24z = 56

18y - 24z = -12       Adding:

-22y = 44

y = -2

So substituting for y in A:

-5(-2) + 3z = 7

3z = 7-10 = -3

z = -1.

Finally, substituting for y and z in the first equation:

2x -(-2) + (-1) = 7

2x + 2 - 1 = 7

2x = 7 - 1 = 6

x = 3.